Exploring Computer Anxiety among Prospective Teachers in Himachal Pradesh, India - Bala, Rajni (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study explores computer anxiety among prospective teachers, defined as the fear or apprehension some individuals experience when using technology. The primary objectives were to assess the overall level of computer anxiety and to examine differences based on gender and academic stream. Utilizing a descriptive survey method, the research involved 100 participants enrolled in a B.Ed. program, comprising 59 females and 41 males, with 53 from the science stream and 47 from the humanities stream. Data were collected using a self-developed Computer Anxiety Scale (CAS) with a reliability coefficient of 0.81. The results indicated a moderate level of computer anxiety across all participants, with no significant differences observed based on gender or academic stream. These findings suggest that while prospective teachers exhibit moderate computer anxiety, this anxiety is consistent regardless of gender or academic background. The study highlights the need for targeted interventions to reduce computer anxiety and enhance technological competence among future educators.